Development and production of sweet corn applied with biostimulant as seed treatment - Lima, Sebastião F.; Jesus, Anderson A.; Vendruscolo, Eduardo P.; Oliveira, Tabata Raissa; Andrade, Maria Gabriela O. [UNESP]; Simon, Cátia Aparecida (FapUNIFESP (SciELO), 2020)
Sweet corn has potential to increase farmer’s income. Thus, biostimulants may contribute to increase productivity of sweet corn, being indicated and used in various crops. The objective of this study was to evaluate the effects of applying biostimulant on sweet corn crops and to establish the ideal dose aiming to increase the crop’s agronomic characteristics. The experiment was installed in the municipality of Chapadão do Sul-MS and was conducted from November 15, 2012 to February 19, 2013. Treatments were composed of eight biostimulant doses (0.0, 4.0, 8.0, 12.0, 16.0, 20.0, 24.0 and 28.0 mL kg-1 of seeds), arranged in a randomized complete block design with four replicates. The responses of the variables to the best dose of biostimulant were 12.4, 15.3, 13.7, 12.4, 15.7, 16.4, 15.4 and 12.5 mL kg-1, respectively for plant height, first ear insertion height, stem diameter, final population, number of ears per hectare, ear mass with and without straw and ear index. Considering that the ear with straw is the source of economic return to the producer, the dose of 16.4 mL kg-1 is the best indication in this condition.
Desenvolvimento e produção do milho doce tratado com bioestimulante
Keywords: Growth regulators; Phytohormones; Rugosa (sweet corn); Saccharata var; Zea mays convar